2019
DOI: 10.2478/lpts-2019-0034
|View full text |Cite
|
Sign up to set email alerts
|

Paraffin Permeability of Synthetic Gypsum Binders Modified by Individual Polymers

Abstract: The paper presents an experimental study of five different gypsum composites taking into account paraffin permeability. The composites consist of synthetic gypsum, paraffin and polymers. The samples were produced from gypsum slurry of mixing ingredients, all in the liquid state. After 7 days of maturing, the condition of the samples was assessed as well as drying time was determined. In the second part, the paraffin tightness of different samples was analysed. The results showed that after three weeks of tests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 28 publications
(25 reference statements)
1
8
0
Order By: Relevance
“…Then he mixed the contents for 2 minutes as the main reason why PCM cannot be connected directly to gypsum is poor mixing properties. A similar relationship was observed in previous studies [26]. When mixing gypsum with PCM, it occurred that PCM did not bind with gypsum while adding water to the mixture.…”
Section: Introductionsupporting
confidence: 88%
See 3 more Smart Citations
“…Then he mixed the contents for 2 minutes as the main reason why PCM cannot be connected directly to gypsum is poor mixing properties. A similar relationship was observed in previous studies [26]. When mixing gypsum with PCM, it occurred that PCM did not bind with gypsum while adding water to the mixture.…”
Section: Introductionsupporting
confidence: 88%
“…The aim of this article has tested compressive strength and bending for the use of this mixture in construction in the form of plasterboard. In previous studies [26], a recipe for combining gypsum with paraffin and polymer was found, while in this study, an attempt was made to prove that the mixture prepared in this way can be used on a real scale, taking into account the further improvement of the composite.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Referring to the previous information on the wide use of gypsum in construction, this article presents research on a specially prepared mixture that can be an alternative to microencapsulation. In addition, the presented research is a continuation of the previous work [32] which allowed for the isolation of essential ingredients and proportions to make the mixture. In this article, the PCM/gypsum composite was subjected to several mechanical tests, and, importantly, from the point of view of thermal properties, it was possible to investigate the thermal conductivity coefficient in the temperature range wherein phase-change material changes its state to liquid.…”
Section: Introductionmentioning
confidence: 84%